Effects of dielectric barrier discharge cold plasma on structure, surface hydrophobicity and allergenic properties of shrimp tropomyosin. (30th May 2023) - Cheng, Jun-Hu; Li, Jilin; Sun, Da-Wen
Highlights: The effect of plasma treatment on structure of TM was studied. IgE binding capacity of TM after plasma treatment was decreased. KU812 degranulation was hindered by plasma treating TM. Allergenicity reduction mechanism and TM structural changes were explored. Abstract: Effects of dielectric barrier discharge (DBD) cold plasma (CP) on structure, surface hydrophobicity and allergenic properties of tropomyosin (TM) in shrimp were investigated in this study. Results showed that the molecular weight of TM increased and the protein concentration decreased with CP treatment time increased. The content of free amino acids was increased by 74.7 % and the distribution of aromatic amino acids was altered. The content of α-helix was decreased by 69 % and the surface hydrophobicity increased by 57.8 % after 20 min treatment. Allergenicity analysis showed that the IgE binding capacity decreased by 96 % after 20 min treatment, and the degranulation indexes of KU812 cells like the β-HEX release rate, the intracellular calcium ion intensity, the release of histamine and inflammatory cytokines (IL-4, TNF-α) were decreased by 32.5 %, 31.0 %, 37.3 %, 51.7 %, and 70.2 %, respectively. The current study confirmed that DBD CP could reduce the TM allergenicity through structural changes.